Analysis of axial and rotational restrained concrete-filled steel tube columns at elevated temperature. (1st March 2023) - Ghannam, Mohamed; Kamrul Hassan, Md
Highlights: Rotational and axial restrained CFST colums under fire is investigated. Verified simplified Finite element (FE) model is developed. Parametric analysis is carried out. A simplified analytical model is proposed. Abstract: This paper has two aims, first, to develop a simplified finite element (FE) model to simulate and study the behaviour of restrained concrete-filled steel tube (CFST) columns subjected to axial force and fire, and second, to propose simplified design equations. FE model has been developed using the ABAQUS program and verified against published data. Furthermore, a parametric study has been conducted using the verified FE model to study different parameters that might affect the behaviour of restrained concrete-filled steel tube columns subjected to axial force under elevated temperatures. These parameters are load level, section type (circular and square), axial and/or rotational restraint ratio, type of steel tube (carbon and stainless steel), type of concrete (carbonate and siliceous concrete aggregate), steel yielding strength, concrete compressive strength, column dimension, width to thickness ratio and reinforcement ratio. Finally, simplified design equations are proposed to determine the buckling time, critical time and maximum load capacity of axial and rotational restrained CFST columns under fire.